Semiotika Puisi “Selamat Pagi, Bumi” Karya M. Faizi - Ach Jazuli; Hasan Busri (Universitas Suryakanca, 2022)
Literary works are the pouring of ideas into texts that contain ethical and aesthetic values. The poem